Implementation of Tolerance Values through Islamic Religious Education Learning at SMAN 1 Karangdowo - Ramdhan, Naida El Nidaa; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines how the values of religious tolerance are taught in Islamic Religious Education (PAI) classes at SMA Negeri 1 Karangdowo, Klaten, and the superior methods used by PAI teachers to achieve this. Data were collected through interviews with PAI teachers, student observations, and document analysis using a descriptive qualitative approach with field and phenomenological approaches. Triangulation and the Miles and Huberman model were used for validation. The findings demonstrate how interactive learning, group projects, extracurricular activities, and teacher role models such as the Prophet Muhammad (peace be upon him) are used to instill the ideals of tolerance. Teachers have effectively built inclusive classrooms that foster social cohesion, tolerance, and respect for individual diversity. To develop the principles of tolerance in schools, collaborative and inclusive learning methodologies and teacher role models are crucial. According to the study's findings, active learning strategies, classroom rules, and teacher role models all play a key role in helping students develop tolerant personalities.